Indonesian Forced-Labour Crew in Chinese Vessel: A Human Rights Perspective (Sociología y tecnociencia, 2021)
The main purpose of this study was to explore the human rights perspective of the recent case of forced-labor Indonesian ship crew in Chinese vessels. Qualitative research methods were used in this research. The data will be collected from related documents such as conventions, laws books, legal journals, and others relevant data associated with the main issue of this research. The data was analyzed by using human rights and international law perspectives, as the legal basis of this research. This research reveals that the Chinese vessel violated the Indonesian ship crew’s human rights. This was found to be an act of slavery indirectly and also was considered as discrimination against certain races where their rights as a human being and laborers were kept deprived in comparison with other ship crew members.
Keywords: Forced labour; Human rights; International Labour Organization.